Announcements (Journal of Financial and Quantitative Analysis, 1974)
The Fourth Annual Meeting of the Financial Management Association will be held on October [24][25][26] 1974, at the Sheraton-Harbor Island Hotel in San Diego, California. The organization's goal is the advancement of knowledge in the area of the financial administration of business, governmental, and nonprofit entities; it emphasizes an interchange between the academic and the practitioner in seeking that goal. The 1974 Annual Meeting has scheduled approximately 40 sessions devoted to a variety of finance topics, including corporation finance, the management of banks and other financial institutions, real estate finance, financial management of health care organizations, consumer finance, and the securities markets.